141k views
5 votes
-6x+11 = 7-10x show all work

User Erik Fubel
by
5.1k points

2 Answers

3 votes
Easy

-6x + 11 = 7 - 10x
Substract 11 from both sides=
-6x = -4 - 10x
Add 10x to both sides
4x = 4
Now divide both sides by the same factor
Answer is x = -1
User Milind Thakkar
by
5.0k points
1 vote

Answer:

Explanation:

collect like terms ( when a negative sign crosses the equality sign it becomes positive and vice versa)

-6x + 10x=7-11

4x=-4

divide both sides by the coefficient of x

4x/4=-4/4

x=-1

User Tjsimmons
by
4.5k points